Spatiotemporal economic impact analysis of the Taal Volcano eruption using electricity consumption and nighttime light data - Ma. Flordeliza P. Del Castillo; Toshio Fujimi; Hirokazu Tatano (Geomatics, Natural Hazards & Risk)
Analyzing the spatiotemporal dimension of the economic impacts of disasters is critical for providing timely and proportionate support. However, traditional economic impact measures often lack spatiotemporal details. Hence, we estimated the daily electricity consumption (EC) loss using high-frequency EC data and analyzed temporal dimensions of the immediate impacts of Taal Volcano’s eruption on January 12, 2020. Subsequently, we computed the nighttime light (NTL) change using high-resolution NTL data to analyze the spatial distribution of these impacts. The temporal analysis revealed two EC loss peaks. The first peak coincided with the power outage and decreased energy demand, followed by a brief recovery after power restoration. The second peak emerged upon the influx of the affected population, evacuees, earthquake occurrences, and road closures. Major assistance distribution spurred recovery towards the end of the analysis period. The spatial analysis showed significant NTL reductions where ashfall intersected built-up areas. The municipalities with the worst NTL reduction included Talisay, Laurel, Santa Teresita, Agoncillo, Lemery, San Nicolas, Taal, and Balete. This study demonstrates an alternative method that uses high-frequency EC to reveal daily temporal fluctuations of immediate non-agricultural economic impacts and map out the areas worst affected by a volcanic eruption.